Adjusting NNP for instrumental or defensive expenditures. An analytical approach - Kjell Arne Brekke; Hanne A. Gravningsmyhr (Statistics Norway, Research Department, 1994)
In this paper we provide a formal analysis to evaluate the subtraction of defensive expenditures from GDP. We consider expenditures that are used to produce non- market goods as candidates for being subtracted from GDP. It will be demonstrated that income net such expenditures will account for total welfare changes only if the supply of the non- market good is constant, while the expenditures should not be subtracted if external factors are constant. We argue that the latter case will apply to most use of the GDP incator for planning purposes. We also consider a model of disamenities of urbanization, and argue that there are important shortcomings in the methods used to estimate these. Daly and Cobb's estimate consideres only a selection of disamenities, and only those that are negative. We also argue that Nordhaus and Tobins migration based procedure will significantly overestimate the level of disamenity, but is correct at the margin. On the other hand, there may be important problems with double counting.
Keywords: D60; H50; H60; R23; 330; Defensive expenditure; National product; Urbanization.